The Influence Of Profitability and Dividend Policy On Financial Performance On Share Price (Study On Himbara Banks Listed On The Indonesia Stock Exchange) Period 2018-2021 - Retno Ambarsari; Hartono; Yuliasnita Verlandes (CV Putra Publisher, 2023)
Economic development in an increasingly modern era has undergone substantial changes; in the business sector, it has developed in line with technological developments, and in the banking sector, which has gone public. This study aims to determine the effect of profitability and dividend policy on financial performance on stock prices at Himbara banks listed on the Indonesian stock exchange. This research uses multiple linear regression methods assisted by data analysis software, namely SPSS 25. The sampling technique used in this research is a saturated sample with a process that uses all population members as samples. The model used in this study was Himbara Bank which consisted of 4 banks, namely Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), State Savings Bank (BTN), and Bank Mandiri. The study results show that profitability partially significantly affects stock prices. It can be seen from the NPM results, which have a t count of 3.264 > t table (2.178) with a probability of 0.009 (p <0.05), ROA with a t count value of 2.595> t table (2.178) with a probability of 0.027 (p <0.05), ROE t count - 2.966> t table (2.178) with a probability value of 0.014 (p <0.05). Dividend policy partially has a significant effect on stock prices. It can be seen from the results (DPS) with a t count of 8,190> t table (2.178) with a probability of 0,000 (p <0.05). As well as profitability and dividend policy simultaneously have a significant influence on the price of Himbara bank shares listed on the Indonesian stock exchange. It can be seen that the result of the F count is 40.304 > F table (3.74), which means that the variable profitability and dividend policy simultaneously affect the stock price.